A patient with an interstitial deletion in Xp22.3 locates the gene for X-linked recessive chondrodysplasia punctata to within a one megabase interval - Klink, Albrecht; Meindl, Alfons; Hellebrand, Heide; Rappold, Gudrun (Human genetics, 1994)
A male patient carrying an interstitial deletion in Xp22.3 and affected by Kallmann syndrome, X-linked ichthyosis and mental retardation, but without chondrodysplasia punctata or short stature, was investigated with molecular probes from the distal Xp22.3 region. By means of a novel probe, M115, from the relevant region, the distal deletion breakpoint was shown to be between 3.18 and 3.57 Mb from Xptel. As the patient is not affected by X-linked recessive chondrodysplasia punctata, the gene for this disease can therefore be located to within an interval of less than one megabase proximal to the pseudoautosomal boundary. If the chondrodysplasia punctata gene is associated with a CpG island, this leaves only two islands at 2760 and 3180 kb from the Xp telomere as the most promising candidate sites for this gene.
Gesehen am 31.03.2021